Web-based Technical Service Work Monitoring Information System at PT PLN (Persero) UP3 Lhokseumawe - Suci Indah Sari; Muhammad Arhami; Amirullah Amirullah (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2024)
PT PLN (Persero) UP3 Lhokseumawe has a data management process for monitoring work and materials which are a means of supporting electricity distribution. Work is a relationship that involves two parties between the company and   workers / employees.  While the material   is   a   tool that   is used   to   meet   the n eeds of employees and the community in supporting the distribution of electricity to the community. At PT PLN (Persero) UP3 Lhokseumawe when collecting data on materials and work still uses Microsoft Excel. If you pay attention, the system that is run is very unsafe, because if the data is lost it cannot be recovered. Therefore, an information system is needed for monitoring technical service work so that the data stored is kept more secure.   The purpose of this research is  to make  a  web-based  system  for monitoring  work  technical  services at  PT PLN (Persero) UP3 Lhokseumawe. Based on the results of system testing using the Black Box Testing (Boundary Value Analysis) method where data entry is very accurate, functionally appropriate. The results of this technical service work monitoring system research are to assist PIC (Person In Charge), supervisors and managers in managing material data, work, stock control and reporting in the planning section.